2022
DOI: 10.1155/2022/6395860
|View full text |Cite|
|
Sign up to set email alerts
|

Empirical Investigation for Predicting Depression from Different Machine Learning Based Voice Recognition Techniques

Abstract: Over the past few decades, the rate of diagnosing depression and mental illness among youths in both genders has been emerging as a challenging issue in the present society. Adequate numbers of cases that have been prevailing had unheard of symptoms linked to mental depression that are able to be detected using their voice recordings and their messages in social media websites. Due to the wide spread usage of mobile phones, services and social sites emotion prediction and analyzing have been an indispensable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It is because these patients are not talkative; rather, they speak with more hesitation and variable pauses that result in a reduced speaking rate, especially by increasing the severity of the problem [11]. Tis is according to Cepstral peak prominence, 2 fundamental frequency, 3 standard deviation of fundamental frequency, 4 harmonic-to-noise ratio, and 5 seconds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is because these patients are not talkative; rather, they speak with more hesitation and variable pauses that result in a reduced speaking rate, especially by increasing the severity of the problem [11]. Tis is according to Cepstral peak prominence, 2 fundamental frequency, 3 standard deviation of fundamental frequency, 4 harmonic-to-noise ratio, and 5 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Finding new methods to determine a disease or predict its progression is a state-of-the-art issue in recent studies, such as using machine learning for Parkinson's disease [ 1 ], hepatitis [ 2 ], and depression disorder [ 3 , 4 ] or analyzing voice acoustics and prosody to determine depression disorder [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%